MEASURING GOVERNMENT PERFORMANCE THROUGH GOVERNANCE INDICATORS: CASE STUDY OF DEVELOPING COUNTRIES - Eric, Ralainirina Razokiny; Emynorane, Ralaivao Hanginiaina; Arrive, Jean Tsitaire; Bien-Aimé, Whega Danitsaike (Journal of Governance and Public Administration, 2025)
This study explores key dimensions of governance in developing countries, with a focus on the factors that influence government effectiveness, institutional integrity, and public accountability. Using a qualitative approach methodology, the study uses documentation analysis as its primary method, drawing on secondary data from reputable sources such as World Bank reports, government documents, and publications by international organizations. The findings highlight persistent challenges faced by developing nations, including weak institutions, limited civic participation, inefficient service delivery, inconsistent regulatory practices, and systemic corruption. Despite numerous reform efforts, progress has often been hindered by lack of political will, inadequate resources, and entrenched power structures. However, the study also identifies examples of best practices and emerging innovations such as digital governance tools and community-based accountability mechanisms that offer potential pathways for improvement. By analyzing these governance dimensions, the study provides a nuanced understanding of the structural and contextual factors that influence governance effectiveness in developing contexts, offering insights for policymakers, development partners, and scholars seeking to promote more inclusive and accountable governance systems.